Analisis Pengaruh Citra Merek, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Kepuasan Dan Loyalitas Konsumen Tempe 5.17 Salatiga - Lia Ardipa; Wulan Ayu Sulistiawati; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This research examines the analysis of the influence of brand image, product quality and service quality on consumer satisfaction and loyalty at Tempe 5.17 Salatiga. The data collection technique uses a questionnaire with 100 respondents. And the data analysis technique uses simple linear regression analysis and multiple linear regression in the processing version using the SPSS 25 program. The results of data analysis show that brand image has a significant effect on satisfaction, satisfaction has a significant effect on consumer loyalty Tempe 5.17, but product quality and service quality variables have no effect on consumer satisfaction Tempe 5.17.